Urban energy handbook : good local practice. - Alexandre, Messrs Ariel; De Michelis, Nicola (OECD, 1995)
This volume presents the results of a seminar which took place in Marseilles, in April 1994. The seminar entitled "Apprenticeship, Alternance and Dual Systems: Dead-Ends or Highways to the Future". It dealt with ways in which alternating learning at school and work can provide young people with relevant work skills, and facilitate their integration in the world of work and-not least-how it may contribute to relate practical and theoretical learning. Part 1 of this volume contains the papers discussed at the seminar and a synthesis of the debate. Part II presents a selection of national contributions to the seminar.